Suppression on allergic airway inflammation of dehulled adlay (Coix lachryma-jobi L. var. ma-yuen Stapf) in mice and anti-degranulation phytosterols from adlay bran. Issue 24 (1st December 2021) - Chung, Cheng-Pei; Lee, Ming-Yi; Hsia, Shih-Min; Chiang, Wenchang; Kuo, Yueh-Hsiung; Hsu, Hsin-Yi; Lin, Yun-Lian
Abstract : This is the first to demonstrate that dehulled adlay suppressed ovalbumin/methacholine induced acute airway inflammation, and phytosterols may be regarded as the indicative anti-degranulation components on anti-allergy. Abstract : Adlay ( Coix lachryma-jobi L. var. ma-yuen Stapf) seeds have been used in Asia for thousands years to treat warts, chapped skin, rheumatism, and neuralgia. The anti-allergic activity of dehulled adlay (DA) seeds was identified, and the bran (AB) is regarded as the main functional constituent in the edible part. However, no study has focused on in vivo acute anti-allergic airway inflammation. In the present report, we investigated DA methanolic extract (DAM) reversed ovalbumin (OVA)/methacholine (Mch)-induced airway hypersensitivity, decreased interleukin (IL)-4, IL-5, and IL-13 levels from splenocytes, suppressed tumor necrosis factor (TNF)-α, IL-1β, and IL-13 levels and reduced eosinophil counts and eotaxin in bronchoalveolar lavage fluid (BALF), which imply that the modulatory effects of DA should involve allergic degranulation. Further, seven phytosterols were isolated from AB ethanolic extract (ABE); among them, 3- O -caffeoyl-5β-sitostan-3-ol, β-sitosterol 3- O -glucopyranoside and β-sitosterol inhibited β-hexosaminidase release from A23187-stimulated RBL-2H3 cells with percentages of 54.1%, 52.0% and 48.5%, respectively, at 50 μM. In addition, β-sitosterol reduced immunoglobulin (Ig)E-stimulated degranulation on RBL-2H3 cells in a dose-dependent manner. The phytosterols were the predominant components based on gas chromatography (GC) analysis. This is the first study to demonstrate that DA suppressed OVA/Mch-induced acute airway inflammation. The phytosterols in AB showed significant anti-degranulation activities, and may be regarded as the indicative components of AB for anti-allergy effects.